2021
DOI: 10.1097/mcg.0000000000001633
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Fecal Microbiota Transplantation for C. difficile Infection in Inflammatory Bowel Disease

Abstract: Background: Fecal microbiota transplantation (FMT) is a safe and effective therapy for recurrent Clostridioides difficile infection (CDI). Data on FMT for CDI in patients with underlying inflammatory bowel disease (IBD) are emerging but conflicting. We performed a systematic review and meta-analysis to describe the efficacy and safety of FMT for CDI in IBD and its impact on IBD outcomes. Methods: A systematic search of multiple databases including Embase, Scopus, and Web of Science was performed. Our primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…The low number of IBD flares encountered in our cohort contrasts with previous studies suggesting exacerbations of IBD after FMT in up to 22% of patients. 19 IBD predisposes to both infection and colonization with C. difficile, probably because of the disturbed microbiota associated with IBD. There are several difficulties related to assessing and treating patients with concomitant IBD and CDI.…”
Section: Discussionmentioning
confidence: 99%
“…The low number of IBD flares encountered in our cohort contrasts with previous studies suggesting exacerbations of IBD after FMT in up to 22% of patients. 19 IBD predisposes to both infection and colonization with C. difficile, probably because of the disturbed microbiota associated with IBD. There are several difficulties related to assessing and treating patients with concomitant IBD and CDI.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The majority of our patient population underwent colectomy for IBD, and previous studies have shown that FMT in IBD patients were effective in treating rCDI and did not result in serious adverse events. 13,14 We demonstrated in our study that FMT is safe to perform in patients who have undergone partial or total colectomy with low rates of CDI recurrence post-FMT.…”
Section: Discussionmentioning
confidence: 55%
“…Some examples include the type of stool received (e.g., fresh versus frozen stools), time from diagnosis of CDI until FMT, severity of CDI or IBD symptoms, mode of delivery, and concomitant medications, among others [1,40]. A systematic review and meta-analysis by Tariq et al concluded that FMT is an effective therapy for rCDI in adult patients with IBD [41]. A similar analysis for pediatric patients has not been completed to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%